2010
DOI: 10.1556/jep.8.2010.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Do they know what they like? Intra-individual variation of female facial preferences

Abstract: Abstract. Although patterns of facial preferences have been examined in many studies, the intraindividual variation in assessments of facial attractiveness has been addressed far less frequently. Here we investigated the stability of women's evaluations of real and digitally manipulated male faces at monthly and yearly intervals, and we sought determinants of the stability. The following results were obtained: (1) The stability of attractiveness assessments over a year was not lower than over a month. This sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…This goes against the common assumption that our preferences are relatively stable and thus, that we only need to account for them once. In support of this, converging evidence is beginning to call the long-held assumption of preference stability into question ( Höfel and Jacobsen, 2003 ; Chen and Risen, 2010 ; Kościński, 2010 ; McManus et al, 2010 ; Pugach et al, 2017 ). The observed instability is commonly attributed to noise within the internal sampling of subjective values.…”
Section: Discussionmentioning
confidence: 99%
“…This goes against the common assumption that our preferences are relatively stable and thus, that we only need to account for them once. In support of this, converging evidence is beginning to call the long-held assumption of preference stability into question ( Höfel and Jacobsen, 2003 ; Chen and Risen, 2010 ; Kościński, 2010 ; McManus et al, 2010 ; Pugach et al, 2017 ). The observed instability is commonly attributed to noise within the internal sampling of subjective values.…”
Section: Discussionmentioning
confidence: 99%
“…This interindividual variability may be due to relative partner preferences (e.g., based on own characteristics and experiences, Figueredo et al, 2006; see a review, Štěrbová and Valentová, 2012). It is also possible, moreover, that an individual’s partner preferences also change over time (Kościński, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This approach revealed differences among various age groups which were due to changes in hormonal levels, personal development, and the like (Kościński, 2011), but it did not track intraindividual variation in preferences in a longitudinal fashion. Kościński (2010) tested individual consistency of facial attractiveness assessment and found that self-correlation of women’s assessment was approximately 0.78, which means that about 40% (1–0.78 2 ) of individual variation in attractiveness rating varies over time. To sum up, existing evidence suggests that preferences can change over time with age and reproductive stage of life, and that they can change in reaction to current circumstances (Rosenthal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the features of live interactions crucial to PPA may explain why in some cases, when isolated participants rated static images, alcohol's effects on PPA did not appear to be mediated by effects on mood . The impact of social context on alcohol‐induced mood enhancement , as well as the effects of alcohol on perception of facial expression , the effects of facial expressions on mood and the effects of mood on attractiveness preferences all reinforce the need to assess the alcohol–PPA association, and its underlying mechanisms, using more ecologically relevant approaches. Further, contrasting static images with more interactive methods would help to isolate the factors (e.g.…”
Section: Discussionmentioning
confidence: 99%